A species‐specific multigene family mediates differential sperm displacement in Drosophila melanogaster. (1st February 2018) - Jayaswal, Vivek; Jimenez, Jamie; Magie, Robert; Nguyen, Kien; Clifton, Bryan; Yeh, Shudan; Ranz, José M.
Abstract: Sperm competition is a postcopulatory sexual selection mechanism in species in which females mate with multiple males. Despite its evolutionary relevance in shaping male traits, the genetic mechanisms underlying sperm competition are poorly understood. A recently originated multigene family specific to Drosophila melanogaster, Sdic, is important for the outcome of sperm competition in doubly mated females, although the mechanistic nature of this phenotype remained unresolved. Here, we compared doubly mated females, second mated to either Sdic knockout or nonknockout males, and directly visualize sperm dynamics in the female reproductive tract. We found that a less effective removal of first‐to‐mate male's sperm within the female's sperm storage organs is consistent with a reduced sperm competitive ability of the Sdic knockout males. Our results highlight the role young genes can play in driving the evolution of sperm competition.